Iniencephaly: A rare anomaly - Shantanu B Chavan (National Journal of Clinical Anatomy, 2019)
Following case report is an attempt to ascertain that the fetus obtained and evaluated presents with iniencephaly, which is one of the rare variants of neural tube defects. Most of the cases of iniencephaly are reported as isolated incidences. However, some researchers have reported its occurrence in cluster, in a short span of time in a specific population. This case report elaborates various gross anomalies in a fetus which differentiates it from other neural tube defects. The study was performed by examining the external features as well as the radiograph of the abortus. The study also elaborates in brief the different versions of neural tube anomalies which are sometimes concomitantly observed in the same fetus. Prenatal or postnatal diagnoses of iniencephaly with or without associated anomalies are suggestive of chromosomal abnormalities and in such cases cytogenetic investigations are highly recommended.